New and little known bees of the genus Colletes Latreille 1802 (Hymenoptera: Colletidae) from Central Asia - Kuhlmann, Michael; Proshchalykin, Maxim Yu. (Zootaxa, 2014)
In addition to a previously published study about Central Asian Colletes bees we here further report on nine rarely collected and little known species. Now 85 species of Colletes are known from this region with three of them recorded for the first time: C. asiaticus Kuhlmann 1999, C. iranicus Noskiewicz 1962 and C. succinctus (Linnaeus 1758). Colletes pseudomirabilis sp. nov. is described from Turkmenistan.